CARICOM Export Development Programme (CCS GeorgetownGY, 1989)
Focuses on four components viz. development and promotion of the common market trade measures and policy instruments; a trade information and marketing advisory service; a Buy-CARICOM programme; and, programme support service. Summaarises the components, elements and project, and provides profiles of the projects. Details the programme schedule, budget and expected outputs.
DC